Complementary Role Of P57kip2 Immunostaining In Diagnosing Hydatidiform Mole Subtypes - Nurzaireena Zainal; Nirmala Chandralega Kampan; Isa M. Rose; Razmin Ghazali; Mohamad Nasir Shafiee; Noor Haliza Yussoff; Azmi Tamil; Muhammad Abdul Jamil; Noor Hamidah Hussin (De Gruyter, 2024)
Indexed by WOS/Scopus/ERA